Effect of hybridisation on crushing behaviour of carbon/glass fibre/epoxy circular-cylindrical shells - Mahdi, E.; Hamouda, A.M.S.; Sahari, B.B.; Khalid, Y.A. (Elsevier Science B.V., 2003)
This study concentrates on the effect of hybridisation on the crushing behaviour, energy absorption and failure mechanism and mode for composite cylinders. The static crushing behaviour of filament wound laminated (FWL) circular-cylindrical composite shell under uniform axial load has been investigated experimentally. Five different hybrids and non-hybrid FWL circular-cylindrical composite shell containing carbon and glass fibres were fabricated. Five types of composites were tested, namely, carbon fibre/epoxy, glass fibre/epoxy, carbon-glass-glass/epoxy, glass-carbon-glass/epoxy and glass-glass-carbon/epoxy. Failure modes were examined using the photographs taken during the different crushing stages for each specimen. Failure modes were highly dominated by the effect of hybridisation. The results also showed that the structure with material sequence of glass-carbon-glass/epoxy exhibited good energy absorption capability.